2023
DOI: 10.3389/fphys.2023.1133423
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial role of exercise in preventing doxorubicin-induced cardiotoxicity

Abstract: Doxorubicin is a highly effective chemotherapeutic agent widely used to treat a variety of cancers. However, the clinical application of doxorubicin is limited due to its adverse effects on several tissues. One of the most serious side effects of doxorubicin is cardiotoxicity, which results in life-threatening heart damage, leading to reduced cancer treatment success and survival rate. Doxorubicin-induced cardiotoxicity results from cellular toxicity, including increased oxidative stress, apoptosis, and activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…It has been reported that Dox-induced killing of cancer cells is mediated by intercalation within DNA base pairs, preventing the synthesis of both DNA and RNA and inhibiting topoisomerase II. Dox also intercalates mitochondrial DNA [89]. This can cause breaks in the mitochondrial DNA, either in one strand or both.…”
Section: Metforminmentioning
confidence: 99%
“…It has been reported that Dox-induced killing of cancer cells is mediated by intercalation within DNA base pairs, preventing the synthesis of both DNA and RNA and inhibiting topoisomerase II. Dox also intercalates mitochondrial DNA [89]. This can cause breaks in the mitochondrial DNA, either in one strand or both.…”
Section: Metforminmentioning
confidence: 99%
“…Several non-pharmacological treatments, like lifestyle modifications, have addressed such adverse events. To date, exercise is one of the most well-researched conservative modalities for mitigating breast cancer patients’ adverse events ( Loprinzi and Cardinal, 2012 ; Palesh et al, 2018 ; Gaytan et al, 2023 ). Indeed, exercise interventions may enhance physical functioning, improve body composition, QoL and autonomic dysfunction, and reduce CRF during chemotherapy or radiotherapy in breast cancer patients ( Courneya et al, 2007 ; Furmaniak et al, 2016 ; Lavín-Pérez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin, an anthracycline antibiotic, is a highly potent chemotherapy drug frequently used to treat a number of malignancies. Even though DOX has strong anticancer properties, its clinical application is constrained by unfavorable side effects such as nephrotoxicity, hepatotoxicity, cardiotoxicity, and gonad toxicity, besides damaging effects on a number of tissues (Öztürk et al 2020 ; Ali et al 2021 ; Alherz et al 2022 , 2023 ; Gaytan et al 2023 ). A well-known rat model of renal failure is DOX-induced nephropathy.…”
Section: Introductionmentioning
confidence: 99%